The Tolerance Value in Habiburrahman El Shirazy’s Novel Ayat-Ayat Cinta 2 - Anis Kurnia Miftahul Husna; Andayani Andayani; Suyitno Suyitno (Institut Agama Islam Negeri Madura, 2017)
The value of tolerance which inherent in the individual soul in this era of globalization began to collapse. Therefore, there are many cases of intolerance that increase every year. The novel of Habiburrahman El Shirazy